Mobile market performance and market structure in Europe during the 4G era - Serafino Abate; Kalvin Bahia; Pau Castells (International Telecommunications Society (ITS), 2020)
This study evaluates the impact of competition on quality, innovation and price in Europe's mobile communications market during the 4G era (2011-18). Our results indicate that European mobile users in more concentrated markets benefitted the most from higher network quality, particularly with regard to download speeds. We find that dispersion of fixed costs and assets among a greater number of players can result in diseconomies of scale and a less efficient use of resources, which translates into lower network performance, to the detriment of consumers. We also find evidence of investment per operator being greater in markets with higher profit margins, which are also typically more concentrated markets.
Keywords: K20; L10; L40; L96; 330